Sarcopenia and Sarcopenic Obesity as Novel Risk Factors for Gastric Carcinogenesis: A Health Checkup Cohort Study - Kim, Young Min; Kim, Jie-Hyun; Baik, Su Jung; Chun, Jaeyoung; Youn, Young Hoon; Park, Hyojin (Frontiers in Oncology, 2019)
Background: Insulin resistance, the primary mechanism of metabolic syndrome, promotes gastric carcinogenesis. Metabolic syndrome is associated with sarcopenia. We aimed to investigate the association between sarcopenia and gastric carcinogenesis, including precancerous conditions such as atrophic gastritis (AG), intestinal metaplasia (IM), and dysplasia. Methods: The study included adult patients who underwent gastroduodenoscopy at a checkup center. AG and IM were evaluated using endoscopy. Based on muscle mass, sarcopenia was defined as a skeletal muscle index <1 standard deviation below the sex-specific mean for healthy adults aged 20–39 years (cutoff point: 29.3% for males and 26.7% for females). Obesity was defined as a body mass index (BMI) ≥25 kg/m2 according to the Asia-Pacific criteria. Sarcopenic obesity was defined as a combination of sarcopenia and obesity. The association between gastric carcinogenesis and sarcopenia was evaluated. Results: Among 8,356 enrolled participants, 0.14 and 42.5% were diagnosed with gastric cancer and precancerous conditions, respectively. Approximately 41.7% of gastric cancer patients and 16.9% of patients with precancerous conditions were diagnosed with sarcopenia. Both sarcopenic obesity (odds ratio [OR] = 4.139, P = 0.016) and diabetes mellitus (DM) (OR = 5.152, P = 0.005) were significantly associated with gastric cancer. Sarcopenia, DM, hypertension, dyslipidemia, Helicobacter pylori infection, smoking, and alcohol consumption were significantly associated with precancerous conditions. Conclusions: Sarcopenia and sarcopenic obesity were associated with gastric carcinogenesis and may be novel risk factors for gastric carcinogenesis.